Pelayanan Imunisasi pada Bayi Selama Pandemi Covid-19 - Marsela, Yenny; Uli, Winda Hotma; Suryanti, Suryanti (Universitas Batam, 2021)
The global Covid-19 pandemic has greatly affected health services. In Indonesia, the Covid-19 pandemic has greatly affected all health services, especially basic health services, including immunization services. There has been a decline in the coverage of basic and advanced routine immunizations in various regions in Indonesia. The burden of immunization-preventable diseases (PD3I) in Indonesia is still very high, so immunization services are very important, especially during a pandemic. Various recommendations for immunization services during the Covid-19 pandemic were issued to ensure immunization services remain a priority for infants and children less than 24 months old in order to prevent the extraordinary events of PD3I.Â